Legal providing of activity of the state on defence of maternity - Suleimenova S.Zh.; Gardt L.A. (Хабаршы. Заң сериясы, 2016)
Actuality of this scientific article is determined swiftly by growing the last years public interest to the questions of defence of maternity and childhood, that it is constrained as with a depth so with character of changes taking place in this sphere. The state is undertaken by responsibility for creation of political, socioeconomic terms in the name prosperity of basic cell of society – family. It is very important for the state and society, that between the constitutionally proclaimed principles and social politics conducted by him there was not a break. Similarly we will take into account coming changes in the labour legislation of Republic of Kazakhstan, considering the category of maternity and labour relations of this institute exactly. And in a conclusion will we draw conclusion : what changes are brought in the institute of public welfare of maternity?